Process-based modeling of arsenic(III) oxidation by manganese oxides under circumneutral pH conditions. (15th October 2020) - Rathi, Bhasker; Jamieson, James; Sun, Jing; Siade, Adam J.; Zhu, Mengqiang; Cirpka, Olaf A.; Prommer, Henning
Highlights: A process-based model for As(III) oxidation by Mn oxides was developed. Literature datasets from both batch and stirred flow (SF) experiments were assessed. A transitional phase and surface passivation were identified in the SF experiment. Overall oxidation rate is controlled by the abundance of edge sites. Mn(III) edge sites play a crucial role in long-term fate of As. Abstract: Numerous experimental studies have identified a multi-step reaction mechanism to control arsenite (As(III)) oxidation by manganese (Mn) oxides. The studies highlighted the importance of edge sites and intermediate processes, e.g., surface passivation by reaction products. However, the identified reaction mechanism and controlling factors have rarely been evaluated in a quantitative context. In this study, a process-based modeling framework was developed to delineate and quantify the relative contributions and rates of the different processes affecting As(III) oxidation by Mn oxides. The model development and parameterization were constrained by experimental observations from literature studies involving environmentally relevant Mn oxides at circumneutral pH using both batch and stirred-flow reactors. Our modeling results highlight the importance of a transitional phase, solely evident in the stirred-flow experiments, where As(III) oxidation gradually shifts from fast reacting Mn(IV) to slowly reacting Mn(III) edge sites. The relative abundance of these edge sites was the most important factor controlling the oxidation rate, whereas surface passivation restricted oxidation only in the stirred-flow experiment. The Mn(III) edge sites were demonstrated to play a crucial role in the oxidation and therefore in controlling the long-term fate of As. This study provided an improved understanding of Mn oxide reactivity and the significance in the cycling of redox-sensitive metal(loid)s in the environment. Graphical abstract: Image, graphical abstract